The Shallot Market Cointegration Between Markets in Province West Southeast and East Nusa Tenggara - Sukma Wati; Doppy Roy Nendissa; Tomycho Olviana; Elfis Umbu K Retang (Garuda Prestasi Nusantara Consulting, 2021)
Abstract West Nusa Tenggara Province is one of the provinces that has become the centre of shallot production in Indonesia, and this situation has made this province, in addition to being able to produce shallots for the needs of its people it is also able to be distributed in other areas, one of which is East Nusa Tenggara Province. And the price of shallots in West Nusa Tenggara Province is much lower than the price of shallots in East Nusa Tenggara Province. The research objective was to determine the long-term relationship between the cost of shallots between Kupang City, Mataram City and Bima City, and the pattern movement of the price of shallots in Kupang City, Mataram City and Bima City. This study uses monthly price data for 2018-2020, the average price of shallots for traditional markets and large traders in the East Nusa Tenggara and West Nusa Tenggara regions. The data analysis method used is the Error Correction Model (ECM) method. This determines whether there is a long-term and short-term relationship between the three markets. The results showed that there was a long-term and short-term relationship between the price of shallots in Bima City and Kupang City, and Mataram City. The situation illustrates that price changes always follow every price change in Mataram in Bima City and Kupang City. Keywords : Shallot, Market, Cointegration, price.